Total car safety suite : heat and smoke sensor using IOT / Aleeyaa Syahira Sharil - Sharil, Aleeyaa Syahira (2024)
In recent years, vehicular safety has evolved beyond conventional measures, embracing technological advancements to mitigate risks and ensure passenger well-being. This project introduces automotive safety by implementing a real-time temperature sensor system within vehicles. The proposed sensor system aims to monitor and regulate interior temperatures, safeguarding occupants from hazardous thermal conditions and enhancing overall driving comfort. This project entails an overview of the proposed car safety temperature sensor system including its objectives, functionalities, potential benefits, and implications for enhancing vehicular safety